Sustainable Hybrid Energy Systems: An Energy and Exergy Management Approach with Homeostatic Control of Microgrids - Cordova-Gonzalez, F (Elsevier B.V., 2015)
Sustainable hybrid energy systems (SHES) are not only possible but can also be affordable for both rural and urban communities. SHES can also replace to a great extent the high cost of utility grids installed power capacity which, in counties like Chile, is outrageously expensive. A new theoretical approach for developing grid-connected SHES is proposed here based on exergy and energy management, cybernetics and homeostatic control (HC), with special emphasis on exergy optimality. The measure of exergy is directly linked to the micro grid system s sustainability index, when understanding that exergy expresses the capacity of the meta-system to do useful work. This capacity is enhanced and augmented whenever energy efficiency (EE) and thriftiness are incorporated into the equation. Thus when consumers behavior becomes an energy source in and of itself, and this is potentiated by the appropriate HC and energy management mechanisms, with appropriate economic incentives for the entire community, the result is that there is much more energy available in the system. Therefore, given a certain amount of energy employed by the overall meta-system, supplied by the SHES and the grid, it is possible to maximize consumers benefits and EE as a whole when supported by individual and collective efforts to ensure the system s overall sustainability. © 2015 Published by Elsevier B.V.